Why are males more attractive after brood care? Proximate causes of enhanced sex pheromone emission in a burying beetle. (21st February 2018) - Chemnitz, Johanna; Fujan, Ina S.; Winkelmann, Carola; Steiger, Sandra
Abstract: Recent studies demonstrate that pheromones can be costly to produce and emit and, therefore, the types and quantities that they express are likely to covary with individual condition. Previous experiments reveal that, when given the opportunity to breed and care for young, male burying beetles Nicrophorus vespilloides go on to produce a higher amount of their sex pheromone and attract more females than control males that do not exhibit parental care. This finding is surprising because parental care is usually assumed to be energetically costly, reducing the future capacity to invest in sexual signalling. However, burying beetles reproduce on dead vertebrates and the carrion meal might enable males to acquire resources that can subsequently be allocated to pheromone signalling. Alternatively, males might accumulate pheromone precursors because they do not emit their sex pheromone during brood care. To shed light on the mechanisms of enhanced pheromone emission after brood care, in the present study, we test the effect of diet quality, social condition during care (biparental versus uniparental care) and an experimentally enforced calling pause on subsequent male pheromone emission, body weight and energy storage components. The experimentally enforced calling pause and social condition during brood care demonstrate no impact on pheromone quantity. However, the results of the present study suggest that the vertebrate carrion meal during brood care partly explains enhanced pheromone release after care. Unravelling the biosynthetic pathways of the pheromone components and analyzing the impact of potential microbial symbionts on pheromone production represents a fruitful avenue for future research. Abstract : The present study aims to shed light on the mechanisms of enhanced sex pheromone emission after brood care in burying beetles. Burying beetles reproduce on vertebrate cadavers and the carrion meal partly explains the enhanced pheromone release after care; an experimentally enforced calling pause has no impact on pheromone quantity. We find no differences in body mass or stored energy components between different nourished beetles and beetles that perform parental care.